2022
DOI: 10.1007/s10661-022-10097-6
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in soils of Mayabeque, Cuba: multifaceted and hardly discernable contributions from pedogenic and anthropogenic sources

Abstract: Cuba is a country with considerable potential for economic growth, and special efforts are made to increase the agricultural output. As food production depends on the quality of soils, heavy metal concentrations were measured in 39 soils in the province of Mayabeque, Cuba, and interpreted in light of anthropogenic activities and pedogenic conditions (soil type and properties). With median concentrations of 1.8 Cd, 60.3 Cr, 48.1 Cu, 36.2 Ni, 16.7 Pb, 55.0 Zn, and 0.1 mg/kg Hg, soils of Mayabeque were mostly bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Agricultural practices, especially fertilizers and pesticides, are another significant source of soil toxic metal/metalloid contamination. An investigation by Sosa et al [15] into the soil composition in Mayabeque, Cuba, revealed the presence of toxic metals/ metalloids such as Cu, Pb, Zn, and Hg, which are significantly influenced by agricultural activities. The study indicated that agricultural runoff, laden with these metals, considerably contributes to their accumulation in soil [15].…”
Section: Introduction To Soil Toxic Metals/metalloidsmentioning
confidence: 99%
“…Agricultural practices, especially fertilizers and pesticides, are another significant source of soil toxic metal/metalloid contamination. An investigation by Sosa et al [15] into the soil composition in Mayabeque, Cuba, revealed the presence of toxic metals/ metalloids such as Cu, Pb, Zn, and Hg, which are significantly influenced by agricultural activities. The study indicated that agricultural runoff, laden with these metals, considerably contributes to their accumulation in soil [15].…”
Section: Introduction To Soil Toxic Metals/metalloidsmentioning
confidence: 99%